New Zealand : 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for New Zealand. (IMF Staff Country Reports; Country Report ;, 2016)
The 2015 Article IV Consultation provides an overview of New Zealand's economic development and policies. Tailwinds have supported the economy's strong growth after the global financial crisis. However, the tailwinds have recently waned. Growth peaked at 3.5 percent year-over-year in the fourth quarter of 2014, bringing output slightly above potential. The exchange rate depreciation has cushioned some of the impact of the decline in dairy prices. The depreciation has mitigated the impact of the international dairy price decline on farmers' incomes and supported exports of travel and education services. Fiscal policy is also supportive of the economy in the short term, while consolidation is projected to resume in the medium term.